The Impact of Systemic Drug Therapies (Bisphosphonates and Immunosuppressants) on Dental Implant Success: A clinical review - Eisa Aldabeab, Khalid; Alsuwaiyan, Asim (Galen Medical Journal, 2024)
Under normal physiological conditions, dental implants are a reliable and effective choice for tooth replacement with high success rates. However, compromised implant success is more closely related to systemic drug therapies like bisphosphonates and immunosuppressants used in patients. This review aims to identify key patterns of implant success and complications among patients undergoing long-term systemic drug therapy and provide clinical recommendations for optimizing outcomes. Bisphosphonates, especially in their intravenous (IV) forms, inhibit osteoclast activity and decrease bone turnover, which may negatively impact osseointegration and increase the incidence of osteonecrosis of the jaw (ONJ). Immunosuppressants are commonly associated with delayed wound healing and a higher risk of infection, complicating implant osseointegration due to their effect on the immune response. Clinicians must adopt personalized approaches to prevent complications in this patient population. Moreover, future studies should aim to explore the long-term effects of systemic drug therapies, particularly regarding dosages, treatment durations, combinations, and newer medications, while investigating drug interactions and dose-response relationships to provide more specific guidelines for clinicians on implant outcomes.